Change in the gender division of domestic work after mummy or daddy took leave: An examination of alternative explanations - Pia S. Schober; Gundula Zoch (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This study investigates how the duration of child care leave taken by mothers and fathers relates to changes in couples' division of housework and child care after postnatal labour market return in Germany. It explores whether take-up of child care related leave may impact the gender division of domestic work beyond the period of leave and examines three theoretical explanations: 1) development of domestic work skills, 2) bargaining power based on economic resources, and 3) adaptations in gender role or parenting identities. Using data from the German Socio-Economic Panel (1992-2012) on 797 and 762 couples with a first or second birth, respectively, we applied OLS regression models with lagged dependent variables in combination with Heckman selection correction. The results suggested that dual-earner couples where mothers took longer leaves experienced a greater shift towards a gender-traditional division of domestic labour after childbirth even in the medium-term after labour market return. The linear relationship and stronger effects on the division of child care than for housework lent support to identity-based explanations. Paternal leave take-up was associated with a more equal division of housework and child care after first births but not after second birth transitions. The relationship with the leave duration was less clear. In terms of explaining the mechanisms for fathers, the findings provided greatest support for explanations relating to domestic skills development possibly in combination with changes in fathering identities.
Keywords: J13; J16; J18; J22; H31; 330; child care; gender division of labour; housework; parenthood; parental leave